2018
DOI: 10.1111/aos.13789
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid levels with primary open‐angle glaucoma: a 5‐year case–control study

Abstract: Primary open-angle glaucoma patients have lower UA levels; however, a negative association between UA levels and disease severity was evident in male patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
5
25
0
Order By: Relevance
“…Moreover, Chang et al [9] performed a small case-control study and found that the concentration of malondialdehyde (MDA) in PACG patients was significantly higher than that of the control subjects. Furthermore, our previous study also reported that the serum level of uric acid, a major antioxidant molecule, was significantly lower in PACG [11] and POAG [12] subjects than that in the control subjects. These results may suggest that evaluating oxidative stress may help in understanding the course of PACG, and oxidative stress damage might be a relevant target for both glaucoma prevention and therapy.…”
Section: Introductionmentioning
confidence: 77%
“…Moreover, Chang et al [9] performed a small case-control study and found that the concentration of malondialdehyde (MDA) in PACG patients was significantly higher than that of the control subjects. Furthermore, our previous study also reported that the serum level of uric acid, a major antioxidant molecule, was significantly lower in PACG [11] and POAG [12] subjects than that in the control subjects. These results may suggest that evaluating oxidative stress may help in understanding the course of PACG, and oxidative stress damage might be a relevant target for both glaucoma prevention and therapy.…”
Section: Introductionmentioning
confidence: 77%
“…During the baseline visit and final follow-up, the subjects underwent a complete ophthalmologic and medical examination [25, 26, 30]. This began with a standardized ophthalmologic examination performed by a glaucoma specialist.…”
Section: Methodsmentioning
confidence: 99%
“…For biochemical measurements, 4 ml of blood was obtained via standard venipuncture at the antecubital fossae (i.e., anterior elbow veins) on the morning after the subjects had fasted for 8 h and had refrained specifically from purine-rich foods (e.g., offal, seafood, and beans) for 2 days. The methods used to calculate UA levels have previously been described in detail [25, 26]. These studies also reported that UA level reference ranges vary in males (0.2023–0.4165 mmol/l) and females (0.1428–0.3392 mmol/l).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following covariates obtained from the claims data were considered as confounders and were adjusted for in the analysis: age, sex, use of other prescribed medications [antidiabetic drugs, antihypertensives, antidepressants, benzodiazepines, anticoagulants, antiplatelet drugs, aspirin, antigout drugs, and non-statins (including fibrates, ezetimibe, and nicotinic acid)], and diagnosis of certain diseases (diabetes mellitus, hypertension, myocardial infarction, chronic heart failure, cerebrovascular disease, renal disorders, liver disorders, pulmonary disease, and cancer). The covariates benzodiazepines, antigout drugs, renal disorders, and liver disorders were included because previous studies have reported that benzodiazepines are associated with acute angle-closure glaucoma [22], serum uric acid levels are associated with primary open-angle glaucoma [23], and nonalcoholic fatty liver disease [24] and hemodialysis [25] are associated with elevated intraocular pressure. The Charlson comorbidity index [26] for prediction of mortality was also calculated using ICD-10 code and included as a covariate.…”
Section: Exposures Outcomes and Covariatesmentioning
confidence: 99%